ROLE OF LONG-TERM INTERMITTENT USE OF ORAL AZITHROMYCIN ON PULMONARY EXACERBATIONS IN CYSTIC FIBROSIS CHILDREN - Abdul Aziz, Danish; Shahid, Shahira; Iftikhar, Haissan; Mir, Fatima (Journal of Ayub Medical College Abbottabad, 2020)
Background: Pulmonary exacerbation is the most common acute event occurring in a patient with cystic fibrosis and Pseudomonas aeruginosa is the most commonly involved organism. Azithromycin have antimicrobial and immunomodulatory effects on lungs and our study aimed to determine the role of long-term intermittent use of oral azithromycin on pulmonary exacerbations in children with cystic fibrosis. Methods: A retrospective cohort study was conducted from January 2012 to December 2016 at a tertiary care hospital, Aga Khan University Hospital, Karachi. The criteria for enrolment included cystic fibrosis patients aged 3-18 years who were classified into two groups based on their antibiotic use. The Azithromycin group included those CF patients who were on three days per week oral Azithromycin (10 mg per Kg per day) for 6 months. The non-azithromycin group included CF patients who were not on long term oral azithromycin. Our primary outcome was to assess the reduction in the number of exacerbations. Results: Sixty-three patients with a mean age (10.06±3.80) and mean pulmonary exacerbations of (3.67±1.58) in the 6 months before enrolment were included in our study. Out of these, 30 patients were included in the azithromycin group and 33 patients in the non-azithromycin group. Overall, 180 exacerbations were documented during the study period. The one-way ANOVA (F (1,61) =8.033, p<0.05) demonstrated a statistically significant difference in the mean number of exacerbations between the azithromycin (2.70±1.72) and non-azithromycin group (3.81±1.40) however, the mean length of stay between the groups was not significant (p=0.582). P. aeruginosa was found to be the most predominant colonizer of the airways. Conclusion: Long term low dose azithromycin therapy is beneficial in young patients with cystic fibrosis. It is an effective prevention strategy for pulmonary exacerbations. Keywords: Cystic Fibrosis, pulmonary Exacerbation, Macrolide